Equivalence Strategy Used In Translating The Hunger Games Novel Into Indonesian - Septiani, Septiani, Dra. Dwi Haryanti, M. Hum, Dr. Anam Sutopo, S.Pd., M. Hum (2013)
The aims of this research are to describe: (1) the linguistic form of equivalence strategy through addition, deletion and shift strategy in translation of the novel entitled The Hunger Games, (2) the dominant strategy used by the translator, (3) the equivalence and non-equivalence of the translation. The type of this research belongs to a descriptive qualitative research where the writer collects the data, arranges, classifies analyzes and concludes the result of the research. The writer uses comparison method which compares source language and target language which consists of equivalence strategy through addition, deletion and shift strategy in chapter 1 of The Hunger Games novel and its translation into Indonesian. The results of the research show that first, there are 109 data or 15,53% belong to addition strategy which containing 87 data or 12,39% of word, 18 data or 2,56% of phrase, 4 data or 0,57% of clause and 0 data or 0% of sentence. Meanwhile in the second strategy which is known as deletion strategy the researcher finds 114 data or 16,24% concludes of 97 data or 13,81% of word, 16 data or 2,28% of phrase, a datum or 0,14% of clause and there is 0 data or 0% of sentence. The last strategy which is called as shift strategy consists 419 data or 59,69% belong to 165 data or 23,50% of word, 180 data or 25,64% of phrase, 31 data or 4,415% of clause and 43 data or 6,125% of sentence. It means that there are more than one strategy in the sentence which used by the translator to achieve the equivalence in the translation of The Hunger Games novel that concludes word, phrase, clause and even sentence. Second, the dominant strategy used by the translator is shift strategy which has 419 data or 59,69%. Third, from the entirely 702 data there are 642 data or 91,45% belong to equivalence while 60 data or 8,55% belong to non-equivalence. As a result, the translation of the novel entitled The Hunger Games into Indonesian is excellent with grade A.